Philosophical Perspectives on Divorce Litigation and Women's Rights in Islamic Family Law: A Study of Indonesian Context - Wahidullah Wahidullah; Rizqul Kamali Maulal Wahid (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The growing tension between Islamic legal formalism and gender-responsive justice has emerged as one of the most contested issues within contemporary Muslim family law, particularly in relation to divorce litigation and women’s post-divorce rights. In Indonesia, the increasing prevalence of wife-initiated divorce cases reflects not only changing marital dynamics, but also deeper transformations in women’s legal consciousness, institutional expectations, and demands for substantive justice. Nevertheless, existing scholarship has largely concentrated on procedural legal analysis and normative doctrinal interpretation, while insufficiently examining the structural contradiction between formal legal recognition and the lived realities experienced by divorced women. This study aims to critically investigate divorce litigation and women’s rights within Indonesian Religious Courts through the integration of substantive justice theory, maqasid al-shari’ah, and sociology of law perspectives. Employing a qualitative socio-legal research design, the study analyzed Religious Court decisions, institutional practices, and semi-structured interviews involving judges, legal advocates, Islamic family law experts, and women’s rights activists. The findings reveal that cerai gugat increasingly functions as a socio-legal mechanism through which women negotiate dignity, protection, and economic survival after prolonged experiences of structural injustice, including domestic violence, financial neglect, and unequal marital power relations. The study further demonstrates that although some judges have adopted progressive and gender-responsive interpretations emphasizing welfare and fairness, the realization of women’s post-divorce rights remains constrained by patriarchal legal assumptions, inconsistent judicial discretion, and weak enforcement systems. Consequently, legal recognition frequently operates only at the symbolic level without producing substantive protection in women’s everyday lives. This study advances contemporary Islamic legal reform discourse by offering a critical socio-legal reconstruction that bridges normative Islamic principles with institutional realities and women’s lived experiences. Ultimately, the research argues that the future legitimacy of Islamic family law depends on its capacity to transform symbolic legality into substantively just, dignity-oriented, and human-centered legal protection.